'Like going into a chocolate shop, blindfolded': What do people with primary progressive aphasia want from speech and language therapy?. Issue 3 (30th November 2022) - Loizidou, Maria; Brotherhood, Emilie; Harding, Emma; Crutch, Sebastian; Warren, Jason D.; Hardy, Chris J.D.; Volkmer, Anna
Abstract: Background: Primary progressive aphasia (PPA) describes a group of language‐led dementias. PPAs are complex, diverse and difficult to diagnose, and therefore conventional models of aphasia and dementia treatment do not meet their needs. The research evidence on intervention for PPA is developing, but to date there are only a few case studies exploring the experiences of people with PPA (PwPPA) themselves. Aims: To explore the experiences and opinions of PwPPA and their communication partners (CPs) to understand how speech and language therapy (SLT) services can better meet their needs. Methods & Procedures: A qualitative research approach was used whereby PwPPA and their friends or family members were recruited to participate in focus groups, via advertisements in the Rare Dementia Support PPA group newsletters. Consenting participants were allocated to attend one of four focus groups hosted on an online video conferencing platform. Participants were asked about their communication difficulties, and how SLT could address these needs. All meetings were transcribed, and data were examined using reflexive thematic analysis. Outcomes & Results: Six PwPPA and 14 CPs representing all three PPA variants and mixed PPA participated in the focus groups. Four main themes were identified during the analysis of the focus group discussions: (1) CPs' burden, (2) adjusting to the diagnosis, (3) communication abilities and difficulties and (4) beyond language. A further 10 subthemes were identified. Conclusions & Implications: This study provides a greater understanding of the experiences and needs of PwPPA and their families in relation to SLT. This work underlines the importance of a person‐centred approach that considers the broader needs of both the PwPPA and the people around them. This will enable service providers to deliver SLT that meets the needs of PwPPA and their families and will also inform future research in this field. WHAT THIS PAPER ADDS: What is already known on this subject: We know that PwPPA can maintain or even make improvements in word retrieval and speech fluency with SLT exercises. There is also developing evidence of the benefits of interventions such as CP training, communication aid support and other functional interventions. What this paper adds to existing knowledge: This study provides an understanding of the experiences and opinions of people living with PPA and their families in relation to SLT. Results demonstrate that PwPPA and their families have to navigate a complex journey, identifying strategies to support communication but also the influence of personality and other cognitive symptoms. SLT was useful, but not always available. What are the potential or actual clinical implications of this work?: This study will enable service providers to better plan, justify funding for and delivery of SLT that will meet the needs of PwPPA and their families. Most importantly this work underlines the importance of a person‐centred approach, incorporating the broader needs of the person with PPA and those around them.